Ten-Year experience with vertical rectus abdominis myocutaneous flap for reconstruction of abdominoperineal resection defects. (March 2021) - LaBove, Gabrielle A.; Evans, Gregory RD; Biggerstaff, Brian; Richland, Brandon K.; Lee, Seung Ah; Banyard, Derek A.; Khoshab, Nima
Abstract: Purpose: We evaluate outcomes of our single center using vertical rectus abdominis myocutaneous (VRAM) flaps for reconstruction after abdominoperineal resection (APR). Our goal was to analyze factors that may affect perineal wound healing, a problematic complication with APR reconstructions due to location and high frequency of neoadjuvant chemoradiation. Methods: This single-center, retrospective study analyzed all VRAM flap perineal reconstruction patients after APR defect over a 10-year period (from July 2008 to June 2018). Outcome measures focused on factors that may affect perineal wound healing complication rates: cancer stage (I/II vs III/IV), neoadjuvant chemoradiation, surgeon's years in practice (<5 years vs >5 years), and pelvic closed suction drain use. Results: Twenty-eight patients met inclusion criteria. The overall major perineal wound complication rate was 14.3% (4 patients). Lack of perioperative closed suction pelvic drain use was associated with a significantly higher rate of major perineal wound complications (28.6% vs 0% and p  = 0.031). All four major wound complications occurred in patients who did not have a pelvic drain. The major perineal wound complication rate for patients who underwent neoadjuvant chemoradiation was 22% vs 0% with no neoadjuvant chemoradiation ( p  = 0.107). Conclusion: While our cohort represents a relatively small single-center study, our 14.3% rate of major perineal wound complications is consistent with previous studies in the literature. Our findings show that perioperative pelvic closed suction drain use is associated with a lower rate of perineal wound complications. While neoadjuvant chemoradiation trended toward a higher incidence of perineal wound complications, it did not reach statistical significance.